Resident involvement in cataract surgery at the Veterans Health Administration: complications, case complexity, and the role of experience. Issue 3 (March 2023) - Aggarwal, Sahil; Wisely, C. Ellis; Pepin, Marc J.; Bryan, William; Raghunathan, Karthik; Challa, Pratap
Abstract : At the Veterans Health Administration, cataract surgeries involving residents had higher intraoperative complication rates than attending-only cases, but these complications were significantly reduced with increasing case volumes. Abstract : Purpose: To characterize intraoperative complications, case complexity, and changes in complication rates with surgical experience for cataract surgeries involving residents at the Veterans Health Administration (VHA). Setting: All VHA facilities where cataract surgery was performed. Design: Multicenter, retrospective cohort study. Methods: A retrospective review of all cataract surgeries within the VHA between July 2010 and June 2021 was conducted. Several parameters, including resident involvement, intraoperative complications, and case complexity as determined by Current Procedural Terminology codes, and use of pupil expansion or capsular support devices, were collected. Complication rates were compared between residents and attendings. Results: Of 392 428 cataract surgeries completed across 108 VHA facilities, 90 504 were performed by attendings alone, while 301 924 involved a resident. Of these, 10 244 (11.3%) of attending cases were complex compared with 32 446 (10.7%) of resident cases. Pupil expansion devices were required in 8191 of attending cases (9.05%) and 31 659 (10.5%) of cases involving residents ( P < .001). Similarly, cases involving residents were more likely than attending-only cases to require a capsular support device (0.835% vs 0.586%, P < .001). Cases involving residents were more likely to have posterior capsular rupture (4.75% vs 2.58%, P < .001) and dropped nucleus (0.338% vs 0.198%, P < .001). Higher resident case volumes were associated with significantly lower complication rates for posterior capsular rupture, dropped nucleus, zonular loss, and suprachoroidal hemorrhage. Conclusions: Although residents had higher intraoperative complication rates than attendings, these rates were reduced with surgical experience. Residents were involved in a similar number of complex surgical cases as attendings.